Pan-Cancer Analysis of NOS3 Identifies Its Expression and Clinical Relevance in Gastric Cancer - Zou, Dan; Li, Zhi; Lv, Fei; Yang, Yi; Yang, Chunjiao; Song, Jincheng; Chen, Yang; Jin, Zi; Zhou, Jinpeng; Jiang, Yang; Ma, Yanju; Jing, Zhitao; et al. (Frontiers in Oncology, 2021)
Background: NOS3 (endothelial NOS, eNOS) is a member of the nitric oxide synthase (NOS) enzyme family, mainly participating in nitric oxide (NO) generation. NOS3 has been reported to inhibit apoptosis and promote angiogenesis, proliferation, and invasiveness. However, the expression pattern of NOS3 and its diagnostic and prognostic potential has not been investigated in a pan-cancer perspective. Methods: Data from the Genotype-Tissue Expression (GTEx), the Cancer Genome Atlas (TCGA), the Cancer Cell Line Encyclopedia (CCLE) and the Cancer Therapeutics Response Portal (CTRP) were employed and NOS3 expression was comprehensively analyzed in normal tissues, cancer tissues and cell lines. Immunohistochemical staining of tissue sections were used to validate the prognostic role of NOS3 in gastric cancer patients. GSVA and GSEA analyses were performed to investigate signaling pathways related to NOS3 expression. Results: In normal tissues, NOS3 was expressed highest in the spleen and lowest in the blood. NOS3 expression was increased in stomach adenocarcinoma (STAD) and significantly associated with poor prognosis of patients. Immunohistochemical staining validated that NOS3 was an independent prognostic factor of gastric cancer. Several canonical cancer-related pathways were found to correlated with NOS3 expression in STAD. The expression of NOS3 was related to the response to QS-11 and brivinib in STAD. Conclusions: NOS3 was an independent prognostic factor for patients with STAD. Increased expression of NOS3 influenced occurrence and development of STAD through several canonical cancer-related pathways. Drug response analysis reported drugs to suppress NOS3. NOS3 might a novel target for gastric cancer treatment.